2011
DOI: 10.1590/s0104-11692011000400016
|View full text |Cite
|
Sign up to set email alerts
|

The experience of thalassemic adults with their treatment

Abstract: This study, based on medical anthropology and oral reports, analyzes the meanings attributed by thalassemic adults to their experiences with the treatment. Interviews were used to collect data, which were analyzed through inductive thematic analysis. Eleven young adults, six of whom were men, at different ages, with different educational levels and occupations participated in the study. The meanings are discussed through the theme "the lives of patients with thalassemia in relation to their treatment". This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…It is believed that lack of immediate consequences of insufficient iron chelation therapy, unavoidably escalates the risk of developing iron overload complications in future ( 10 , 20 ). In line with our findings, previous studies found that delay in the occurrence of complications can potentially lead to discontinued or irregular following of prescribed regimens by the patients ( 18 , 19 ). Therefore, healthcare providers need to continually emphasize the importance of regular chelation therapy and assessment of body iron to patients for improving their survival chance ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is believed that lack of immediate consequences of insufficient iron chelation therapy, unavoidably escalates the risk of developing iron overload complications in future ( 10 , 20 ). In line with our findings, previous studies found that delay in the occurrence of complications can potentially lead to discontinued or irregular following of prescribed regimens by the patients ( 18 , 19 ). Therefore, healthcare providers need to continually emphasize the importance of regular chelation therapy and assessment of body iron to patients for improving their survival chance ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, previous studies found that delay in the occurrence of complications can potentially lead to discontinued or irregular following of prescribed regimens by the patients ( 18 , 19 ). Therefore, healthcare providers need to continually emphasize the importance of regular chelation therapy and assessment of body iron to patients for improving their survival chance ( 18 , 19 ). Another two important barriers of adherence to treatment were staff’s heavy workload and insufficient follow-up of healthcare providers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This process can reduce the liver iron burden and the incidence of functional disorders of the heart, pancreas, and other organs. Besides, it improves growth and sexual maturation and extends the patients' life span [6]. Before and after the deferoxamine initiation, it is necessary to regularly measure the patient's serum ferritin level (every 6 months) [7].…”
Section: Introductionmentioning
confidence: 99%